Filamin C variants are associated with a distinctive clinical and immunohistochemical arrhythmogenic cardiomyopathy phenotype. (15th May 2020) - Hall, Charlotte L.; Akhtar, Mohammed M.; Sabater-Molina, Maria; Futema, Marta; Asimaki, Angeliki; Protonotarios, Alexandros; Dalageorgou, Chrysoula; Pittman, Alan M.; Suarez, Mari Paz; Aguilera, Beatriz; Molina, Pilar; Zorio, Esther; et al.
Abstract: Background: Pathogenic variants in the filamin C ( FLNC) gene are associated with inherited cardiomyopathies including dilated cardiomyopathy with an arrhythmogenic phenotype. We evaluated FLNC variants in arrhythmogenic cardiomyopathy (ACM) and investigated the disease mechanism at a molecular level. Methods: 120 gene-elusive ACM patients who fulfilled diagnostic criteria for arrhythmogenic right ventricular cardiomyopathy (ARVC) were screened by whole exome sequencing. Fixed cardiac tissue from FLNC variant carriers who had died suddenly was investigated by histology and immunohistochemistry. Results: Novel or rare FLNC variants, four null and five variants of unknown significance, were identified in nine ACM probands (7.5%). In FLNC null variant carriers (including family members, n = 16) Task Force diagnostic electrocardiogram repolarization/depolarization abnormalities were uncommon (19%), echocardiography was normal in 69%, while 56% had >500 ventricular ectopics/24 h or ventricular tachycardia on Holter and 67% had late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (CMRI). Ten gene positive individuals (63%) had abnormalities on ECG or CMRI that are not included in the current diagnostic criteria for ARVC. Immunohistochemistry showed altered key protein distribution, distinctive from that observed in ARVC, predominantly in the left ventricle. Conclusions: ACM associated with FLNC variants presents with a distinctive phenotype characterized by Holter arrhythmia and LGE on CMRI with unremarkable ECG and echocardiographic findings. Clinical presentation in asymptomatic mutation carriers at risk of sudden death may include abnormalities which are currently non-diagnostic for ARVC. At the molecular level, the pathogenic mechanism related to FLNC appears different to classic forms of ARVC caused by desmosomal mutations. Highlights: FLNC -linked ACM presents with LV involvement, ventricular arrhythmia, sudden death. Late gadolinium enhancement on cardiac MRI may be the only structural abnormality. Mutation carriers have abnormalities on ECG or cardiac MRI non-diagnostic for ARVC. FLNC disease mechanism different to classic ARVC caused by desmosomal mutations.